Online investing on the Australian sharemarket - Kinsky, Roger (John Wiley & Sons, Inc., 2020)
The complete guide to trading and researching the Australian sharemarket online, fully revised and updated It has never been easier to use the internet to trade and invest in the Australian sharemarket. Thanks to the wide availability of online brokers and financial websites, online market data, low cost broadband and trading sites and user-friendly digital platforms, a growing number of Australians are taking more direct control of their investments and wealth management. Online Investing on the Australian Sharemarket is a comprehensive guide to researching and trading shares and other securities online in Australia. This popular book offers step-by-step guidance on choosing an online broker, accessing and making best use of online share investing resources, planning trades, identifying profit-making opportunities, timing of and placing online orders, managing investment risks, and much more. Bestselling author and successful trader Roger Kinsky provides a step-by-step process for harnessing the power of the internet to make informed and profitable trading and investment decisions. Now in its fifth edition, this time-proven resource features extensively revised content and up to date information throughout. Featuring real-world advice and practical tips drawn from the author's decades of online share investing experience, this valuable guide will: explain the basic concepts, terminology, and advantages of online investing and share trading explore how to avoid the potential pitfalls and common mistakes that might otherwise occur examine the different types of financial websites, data, information, tools, and other resources available online provide guidance on fundamental and technical analysis, online charting and indices, and strategic risk management Offering authoritative information and proven trading strategies, Online Investing on the Australian Sharemarket, Fifth Edition is essential reading both for those new to the market and more experienced investors alike.